Analysis Of Genetic Structure Of Nigerian West African Dwarf Goats By Microsatellite Markers markers (2015)
Genetic variation at 12 microsatellite loci and population structure hypothesis was examined for West African Dwarf (WAD) goat populations found in four Southwestern states in Nigeria. Estimates of genetic variability such as effective number of alleles and gene diversities revealed substantial genetic variation frequently displayed by microsatellite markers. Number of alleles observed across the microsatellite loci varied from 6 to 17 with an overall mean of 10.75 ± 3.22. Average polymorphism across the studied loci and expected gene diversity in the population were 1.66 ± 0.49 and 0.72 ± 0.17, respectively. Population was observed to be significantly differentiated into different groups, and showed fairly high level of inbreeding (f = 0.95 ± 0.15) and global heterozygote deficit.